(untitled) (Annals of Medical Research, 2023)
Aim: Maternal hyperoxygenation (MHO) has been recommended as an alternative treatment for fetuses with IUGR. We wanted to evaluate the effect of MHO treatment on ductus venosus (DV) and pulmonary vein (PV) doppler flow measurements in fetuses with late-onset IUGR. Materials and Methods: A total of 63 pregnant women were enrolled in the study (32 pregnant women diagnosed with IUGR and 31 women with normal growth). The control group comprised 31 randomly selected age-matched and gestational-age-matched healthy pregnant women who presented to the antenatal clinic on the exact dates as the women in the study group. Results: In the IUGR group, MHO significantly increased the PI value of DV (0.50 (0.40, 0.58) to 0.62 (0.60, 0.65). p<.001). The DV-S, DV-D, and S/a values of the DV increase significantly for the IUGR group. DV- a value of DV decreased significantly from 52.00 (49.25, 52.75) to 41.50 (38.50, 42.75) p<.001. Comparison of Doppler findings in healthy fetuses before and after oxygen inhalation did not change significantly. Also, The PI value in the PV did not change significantly following maternal hyper oxygenation in the IUGR group (pre-O2: 0.80 (0.73, 0.88) and post-O2: 0.80 (0.70, 0.90)). Conclusion: We detected a statistically significant increase in both DV and PV blood flow during MHO administration in late-onset IUGR fetuses. Since increased DV and PV blood flow is associated with increased cardiac output, we think that it will reduce hypoxia in fetuses with IUGR.